Heavy Metals Accumulation in Some Vegetables and Soils in Istanbul - (:unkn) unknown (FOUNDATION ENVIRONMENTAL PROTECTION & RESEARCH-FEPR, 2012)
This work was designed to assess the concentration of six toxic metals in the soil and in unwashed and washed samples of different vegetable species (Petroselinum crispum, Brassica oleraceae var. acephala, Beta vulgaris var. cicla collected from six different sites (stream side, inner city, industrial, suburban, roadside, and rural) in Istanbul in 2007. Concentrations of Cd, Cr, Cu, Ni, Pb, and Zn were determined by using ICP-OES. It was found that the average highest values of metal accumulations were detected in unwashed samples. The correlation was significant between metal accumulations and the sites, where the vegetables were grown, in the industrial areas and along the roadsides. The highest and lowest average values in the vegetables varied between 0.24-0.89 mu g/g dw for Cd, 3.73-14.04 mu g/g dw for Cr, 1.47-5.19 mu g/g dw for Cu, 3.13-13.65 mu g/g dw for Ni, 29.28-87.00 mu g/g dw for Pb, and 3.48-5.74 mu g/g dw for Zn. The pattern of total metal contrations in the vegetables followed Pb > Cr > Ni > Zn > Cu > Cd.
Keywords: Heavy metal; Istanbul; pollution; vegetable; TRACE-METALS; TURKEY; BIOMONITOR; POLLUTION; PROVINCE; PLANTS; URBAN; ZN; PB; NI